The Role of Management in Increasing Students’ Satisfaction: Investigating Culture, Price and Reputation of Universities of Pakistan - Urooj Fatima; Zhang Junchao; Daniyal Khan (European Scientific Journal, ESJ, 2019)
Title: this research paper investigates the role of university management in increasing students’ satisfaction by checking the role of culture, price and reputation of universities of Pakistan. Management qualities of a university plays an important role in the development of students’ satisfaction, and directly or indirectly influences their satisfaction level. It is argued that university management should focus on culture development and lowering down tution price to increase satisfaction level and reputation of the university. This study made use of 5-point Likert scale questionnaire to find out the management quality factors. A total of 150 students from different universities were investigated through this questionnaire. SPSS 21 software was used for the investigation through regression and correlation analysis. Convenience sampling method was used, due to lack of time and resources for approaching the respondents. Only the university respondents were inquired to find out their satisfaction level. The results obtained were segmented into six hypothesis. Five hypothesis were accepted. It was found that students were not satisfied with management quality and culture of their universities. While correlation between management quality and students’ satisfaction was found positive. The students are not happy with service timing and its quality provided by the university management. The relationship between university reputation and management quality through correlation was found to be negative. Tution fee of the investigated universities is very high, which is also a reason students’ do not like service quality even after paying high fees.